Mathematical Model for Analyzing Heat Transfer Characteristics of Ablative Thermal Insulating Material - Junjie Gao; Haitao Han; Daiying Deng; Jijun Yu (International Journal of Aerospace Engineering)
A mathematical model based on minimal thermal resistance and equal law of specific equivalent thermal conductivity is developed to discuss the heat transfer characteristics of ablative thermal insulating material from the mesoscopic scale. Based on the statistical results of mesoscopic parameters, the microstructure unit cell model was established to analyze the influence rule of mesoscopic parameterization which includes the size, distribution, and positional relation of microsphere and fiber. The results show that the equivalent thermal conductivity decreases with the density, size, distribution area, and distance of microsphere and the space distance and volume fraction of fiber decreasing. Besides, the equivalent thermal conductivity will become larger when more quality of heat transfers along the fiber direction. Exploring the relationship between the macroscopic heat transfer process and the microstructure is meaningful for exploring the heat transfer behavior of thermal insulating material and improvement of the processing technology.